Hypertension-Related Gene Polymorphisms of G-Protein-Coupled Receptor Kinase 4 Are Associated with NT-proBNP Concentration in Normotensive Healthy Adults - Junichi Yatabe; Midori S. Yatabe; Minoru Yoneda; Robin A. Felder; Pedro A. Jose; Hironobu Sanada (International Journal of Hypertension)
G protein-coupled receptor kinase 4 (GRK4) with activating polymorphisms desensitize the natriuric renal tubular D1 dopamine receptor, and these GRK4 polymorphisms are strongly associated with salt sensitivity and hypertension. Meanwhile, N-terminal pro-B-type natriuretic peptide (NT-proBNP) may be useful in detecting slight volume expansion. However, relations between hypertension-related gene polymorphisms including GRK4 and cardiovascular indices such as NT-proBNP are not clear, especially in healthy subjects. Therefore, various hypertension-related polymorphisms and cardiovascular indices were analyzed in 97 normotensive, healthy Japanese adults. NT-proBNP levels were significantly higher in subjects with two or more GRK4 polymorphic alleles. Other hypertension-related gene polymorphisms, such as those of renin-angiotensin-aldosterone system genes, did not correlate with NT-proBNP. There was no significant association between any of the hypertension-related gene polymorphisms and central systolic blood pressure, cardioankle vascular index, augmentation index, plasma aldosterone concentration, or an oxidative stress marker, urinary 8-OHdG. Normotensive individuals with GRK4 polymorphisms show increased serum NT-proBNP concentration and may be at a greater risk of developing hypertension and cardiovascular disease.